ABUNDANCE AND DIVERSITY OF ENTOMOPATHOGENIC FUNGI IN SIBOLANGIT CONSERVATION FOREST AND BERASTAGI VEGETABLE LAND - Sularno Sularno; Edi Azwar; Yusri Fefiani (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to determine the diversity and abundance of entomopatogenic fungi that exist around the Brastagi vegetable field and Sibolangit conservation forest. From the results of the study it was found that the Sibolangit Conservation Forest found 2 types of entomopatogenic fungi Beauveria bassiana and Metarhizium anisopliae. The level of abundance is quite low, namely the highest average larvae infected by B.bassiana 3 larvae per sample site and 2 larvae infected with Metarhizium per sample soil. While infection in larvae is higher in the Berastagi community vegetable garden. From the vegetable garden, the Berastagi community found 2 types of entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae. The level of abundance is higher than that of fungi originating from sibolangit conservation forests, namely the highest average larvae infected by B.bassiana 5 larvae per sample soil location and 3 larvae infected with Metarhizium per sample soil. Keywords: Entomopatogenic fungi, exploration, isolation, diversity, abundance